2008
DOI: 10.1007/s12264-008-1221-0
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X syndrome and epilepsy

Abstract: Fragile X syndrome (FXS) is one of the most prevalent mental retardations. It is mainly caused by the loss of fragile X mental retardation protein (FMRP). FMRP is an RNA binding protein and can regulate the translation of its binding RNA, thus regulate several signaling pathways. Many FXS patients show high susceptibility to epilepsy. Epilepsy is a chronic neurological disorder which is characterized by the recurrent appearance of spontaneous seizures due to neuronal hyperactivity in the brain. Both the abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Osmolytes control the ion gradient across membranes, and modifications of their levels may facilitate neuronal discharge and epileptiform activity (Liu et al 2008), as described in the Fmr1-deficient mouse (Qiu et al 2008). …”
Section: Altered Osmolyte and Secondary Messengers Balancementioning
confidence: 99%
“…Osmolytes control the ion gradient across membranes, and modifications of their levels may facilitate neuronal discharge and epileptiform activity (Liu et al 2008), as described in the Fmr1-deficient mouse (Qiu et al 2008). …”
Section: Altered Osmolyte and Secondary Messengers Balancementioning
confidence: 99%
“…Clinical FXS symptoms include delayed and depressed developmental trajectories (Bailey et al, 2001a,b; Hall et al, 2008), short-term working memory deficits (Munir et al, 2000; Cornish et al, 2001; Kwon et al, 2001; Lanfranchi et al, 2009), disordered sleep (Gould et al, 2000; Miano et al, 2008), seizures (Kluger et al, 1996; Musumeci et al, 1999; Singh et al, 1999; Sabaratnam et al, 2001; Berry-Kravis, 2002; Di Bonaventura et al, 2006; Qiu et al, 2008), elevated anxiety (Tsiouris and Brown, 2004), and attention-deficit hyperactivity disorder (Hatton et al, 2002; Sullivan et al, 2006). Significantly, 30% of FXS patients are also diagnosed with autism (Figure 1) (Kau et al, 2004; Hagerman, 2008b; Harris et al, 2008).…”
Section: Fragile X Syndromementioning
confidence: 99%
“…While the GABA A receptor has been proposed as a potential target for the treatment of FXS (D'Hulst & Kooy 2007; Heulens et al . 2010), it has been suggested that agonists may have no effects on the genesis of spontaneous seizures (Qiu et al . 2008).…”
Section: Aetiological Mechanisms Underlying Epilepsy and Intellectualmentioning
confidence: 99%